Marketing innovation and internationalization in smart city development: a systematic review, framework and research agenda. Issue 5 (7th April 2021) - Christofi, Michael; Iaia, Lea; Marchesani, Filippo; Masciarelli, Francesca
Abstract : Purpose: Smart cities and their internationalization process and efforts in order to gain the competitive advantage in the international arena have received a great deal of attention by marketing scholars and practitioners alike. Yet, the growing number of studies focused on this topic has led to considerable fragmentation and theoretical confusion. Design/methodology/approach: To move the domain forward, this study applies the systematic review methodology and reviews 41 peer-reviewed articles published in highly esteemed publication outlets. Findings: Building on the antecedents–phenomenon–consequences framework, the authors discuss the antecedents and consequences of the various innovative marketing strategies that smart cities adopt for their internationalization and development of an international competitive advantage. In the process of doing so, the authors synthesize the findings of the studies as well as literature gaps that provide fruitful avenues for future research. Originality/value: This article offers a systematic review of extant marketing research on smart cities and their efforts to internationalize. In particular, this study advances the conceptual development of smart city internationalization and innovation by a marketing lens, provides an integrative, international-oriented framework that maps the extant literature across disciplines and countries, expands the boundaries of this research domain into new research paths and offers implications for policy and practice.